Organic farming has little effect on carbon stock in a Mediterranean dehesa (southern Spain) - Parras-Alcántara, Luis; Díaz-Jaimes, Luisa; Lozano-García, Beatriz; Fernández Rebollo, Pilar; Moreno Elcure, Félix; Carbonero Muñoz, María D (CATENA, 2014)
Understanding soil dynamics is essential for making appropriate land management decisions, as soils can affect the carbon content from the atmosphere, emitting large quantities of CO2 or storing carbon. This property is essential for climate change mitigation strategies as agriculture and forestry soil management can affect the car- bon cycle. The Mediterranean dehesa (Mediterranean grassland ecosystem with scattered oak trees — grazing systemwith Quercus ilex spp. ballota) is a silvopastoral systemthat integrates forestry, agricultural and livestock practices. The dehesa is characterized by the preservation of forest oaks that provide environmental services includingcarbon capture and storage.Thispaper showsthe relationships betweensoilproperties andsoil organic carbon (SOC) in two soil types: Cambisols (CM) and Leptosols (LP), with two management systems: organic farming (OF) for 20 years and conventional tillage (CT) in a Mediterranean dehesa of southern Spain without cropping. An analysis of 85 soil profiles was performed in 2009 in Los Pedroches Valley (Cordoba, southern Spain). TheSOCstock (SOC-S)was greater inCM(75.64 Mg ha−1)thaninLP(44.01 Mg ha−1). Physical parameters were themain variables affecting soil development. SOC-S was very similar in OF and CT (CM [74.90 Mg ha−1-CT; 76.39 Mg ha−1-OF] and LP [44.77 Mg ha−1-CT; 43.25 Mg ha−1-OF]). Data analysis showed that management practices had little effect on SOC storage in the study zone. Significant differences between soil types and manage- ment practiceswere found in SOC content for different horizons. The stratification ratiowas N2in bothsoils types (CM and LP) and management systems (OF and CT). These results indicate that the soil is of high quality, and that management practices have little influence on SOC-S in Los Pedroches Valley.
Keywords: Conventional tillage; Management practices; Organic farming; Quercus ilex; Soil organic carbon

Average daily weight gain of Iberian fattening pigs when grazing natural resources - Rodríguez-Estévez, Vicente; Sánchez-Rodríguez, Manuel; García, Antón R.; Gómez-Castro, a Gustavo (Livestock Science, 2011)
In spite of the growing interest in organic farming and sustainable production, there is a lack of information about the performance of pigs when they feed only on natural resources. This research studied the fattening pattern during the montanera (free-range grazing on acorns and grass during autumn and winter, without any supplementary feed or mineral complement) of the Iberian pig in the dehesa (Quercus ilex open woodlands) in order to know the average daily gain (ADG) and to analyze the inﬂuence of three factors: year of montanera, age and sex of pigs. The fattening data were obtained from two ﬂocks of castrated pigs during the ﬁrst two months (from November the ﬁrst) of two consecutive montaneras (2003 and 2004) on the same farm. Pigs (from 111.8± 0.9 kg BW at introduction) were individually weighed every 15 days in the early morning, with no food intake since the previous evening. The ADG for all pigs was 0.76± 0.01 kg/day; however, some variations were observed according to the year (0.74±0.02 kg/day in 2003 vs. 0.78±0.02 kg/day in 2004; pb0.05), the sex (0.78±0.02 kg/day for males vs. 0.72± 0.02 kg/day for females; pb0.01) and the age (0.71±0.02 kg/day for pigs younger than a year vs. 0.83±0.02 kg/day for pigs older than a year; pb0.001); however a factorial 3-way ANOVA does not show signiﬁcant interaction between factors. Comparing the fortnights periods, the lowest ADG was measured in the ﬁrst 15 days of montanera (0.60±0.02 kg/day), and the highest ADG occurred in the second one (0.85±0.02 kg/day). Later on, the datasets were adjusted with the GLM procedure for the fixed effects of the year of the montanera, the age and the sex. With the adjusted datasets, different regression models for the fattening in montanera were established; the best adjusted of those was the potential model (Y= 0.32*X 1.22 ; X= days of montanera; and Y= kg life weight gained during the montanera). According with this model pigs would need an average of 58 d to fatten 46 kg, as the Iberian Breed Quality Standards demand. Finally, the results show that the age and sex, as factors that inﬂuence the ADG, should be taken into close account to choose pigs and that it is possible to reach a high ADG grazing only with natural resources, following appropriate management strategies such as rationing in order to obtain the beneﬁts of compensatory growth.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: acorn; Compensatory growth; Extensive farming; Free ranging; Grass; Organic farming; Sustainable production

Caracterización productiva del vacuno ecológico en Andalucía - Perea Falcón, J; García, Ana; Acero, R; Valerio, Daniel; Rodríguez, V (Arch. Zootec, 2007)
The structure of organic beef cattle farms located in Andalusia have been characterised from a stratified survey including 10% of official census. Farms are specialized in raising steers and use native breeds. The mean surface of farms is 524 ha and they have 99 cows. They are multifunctional systems located in the dehesa, where cattle commonly graze alongside other species like Iberian pigs. These farms correspond to a production model in which the land is extremely important in the production of food for the cattle, using strategic or seasonal food supplementation in periods of shortage. Average stocking is 0.43 animals/ha, lower than those proposed by Orden de 4 de febrero del 2004 (Consejería de Agricultura y Pesca), corresponding to a farming activity adapted to the environment. Likewise, the mean productivity of these farms is scarce (with an index of commercial calves of 80% and a mortality rate of 5.26%). These farms have a commercial target where the non-familiar workforce predominates, and the workforce amounts to 1.56 AWU per farm. These farms sell all calves after weaning to livestock traders, who take them to other regions for conventional fattening until slaughter. It is necessary to develop organic commercial trails to guarantee the future of the sector.
Keywords: Beef aptitude; Extensive systems; Organic farming

Caracterización productiva del vacuno ecológico en Andalucía - Perea Falcón, J.; García, Ana; Acero, R.; Valerio, Daniel; Rodríguez, V. (Arch. Zootec, 2007)
The structure of organic beef cattle farms located in Andalusia have been characterised from a stratified survey including 10% of official census. Farms are specialized in raising steers and use native breeds. The mean surface of farms is 524 ha and they have 99 cows. They are multifunctional systems located in the dehesa, where cattle commonly graze alongside other species like Iberian pigs. These farms correspond to a production model in which the land is extremely important in the production of food for the cattle, using strategic or seasonal food supplementation in periods of shortage. Average stocking is 0.43 animals/ha, lower than those proposed by Orden de 4 de febrero del 2004 (Consejería de Agricultura y Pesca), corresponding to a farming activity adapted to the environment. Likewise, the mean productivity of these farms is scarce (with an index of commercial calves of 80% and a mortality rate of 5.26%). These farms have a commercial target where the non-familiar workforce predominates, and the workforce amounts to 1.56 AWU per farm. These farms sell all calves after weaning to livestock traders, who take them to other regions for conventional fattening until slaughter. It is necessary to develop organic commercial trails to guarantee the future of the sector.
Keywords: Beef aptitude; Extensive systems; Organic farming